2015
DOI: 10.3892/ijmm.2015.2252
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and expression analysis of mouse epidermal growth factor-like domain 8

Abstract: Abstract. Epidermal growth factor (EGF)-like (EGFL)domain, a common structural module in numerous secreted or transmembrane proteins, is generally involved in protein-protein interactions. To date, several EGFL proteins have been identified and characterized, but little is known about EGFL domain 8 (EGFL8). The present study reported the molecular characterization and expression analysis of EGFL8 in mice. Mouse EGFL8 amplified using a reverse transcription-polymerase chain reaction approach was sequenced and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Epidermal growth factor‐like domain multiple 6 (EGFL6) is an extracellular matrix protein, belongs to EGFL family and plays an important role in promoting the migration and angiogenesis of endothelial cells . Recently, it is reported that EGFL6 regulates the metastasis of ALDH + ovarian cancer cells and is overexpression in benign meningioma and oral squamous cell carcinoma . Moreover, EGFL6 implicates in the pathogenesis of benign meningioma via activating AKT pathway .…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor‐like domain multiple 6 (EGFL6) is an extracellular matrix protein, belongs to EGFL family and plays an important role in promoting the migration and angiogenesis of endothelial cells . Recently, it is reported that EGFL6 regulates the metastasis of ALDH + ovarian cancer cells and is overexpression in benign meningioma and oral squamous cell carcinoma . Moreover, EGFL6 implicates in the pathogenesis of benign meningioma via activating AKT pathway .…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences were observed in the expression of EGFL gene family among different types of tumors, as well as among different members of EGFL family within each tumor type, demonstrating the need to study each gene member as a separate entity. In tumorigenesis, one typical functional feature of these genes was their expression dysregulation in tumors, and increasingly, evidence supported the conclusion that the expression of the EGFL family members changes in different tumors (Wu et al, 2011a;Nichol and Stuhlmann, 2012;Song et al, 2015). However, the majority of the evidence has been provided by the studies on cell lines or animal models.…”
Section: Egfl Domains Gene Expression In Pan-cancermentioning
confidence: 96%
“…EGFL6, 7, and 8 have been partially studied in CRC (Song et al, 2015;Hong et al, 2018;Zhang et al, 2019). In this study, TCGA CRC data were used to conduct a comprehensive study of EGFL genes in one of the largest CRC patient cohort publicly available.…”
Section: Egfl Domain Gene Family In Colorectal Cancermentioning
confidence: 99%
See 2 more Smart Citations